Peran Kepuasan Hidup dalam Pengelolaan Penyakit Systemic Sclerosis - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Ika Sandra Dewi; Romaito Nasution; Milna Sari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
This study examines life satisfaction's role in managing Systemic Sclerosis (SSc) through a comprehensive meta-analysis. Out of 1,247 identified articles, 42 studies met the inclusion criteria, encompassing 8,734 SSc patients. The findings reveal a significant positive correlation between life satisfaction and treatment adherence in Systemic Sclerosis (r = 0.39, 95% CI [0.32, 0.45], p < 0.001), utilizing adaptive coping strategies (r = 0.45, 95% CI [0.38, 0.51], p < 0.001). Additionally, life satisfaction was negatively correlated with depression (r = -0.52, 95% CI [-0.58, -0.45], p < 0.001) and anxiety (r = -0.47, 95% CI [-0.54, -0.39], p < 0.001). Social support emerged as a strong predictor of life satisfaction (r = 0.51, 95% CI [0.44, 0.57], p < 0.001). Furthermore, interventions aimed at enhancing life satisfaction demonstrated a significant positive effect (d = 0.62, 95% CI [0.45, 0.79], p < 0.001). Moderator analyses indicated that age and disease duration influenced the strength of the relationship between life satisfaction and SSc management. The researchers believe these findings extend previous studies by Kwakkenbos et al. (2015) and Malcarne et al. (2013) by quantifying the strength of the relationship between life satisfaction and various aspects of SSc management on a larger scale. Unlike the findings of Thombs et al. (2010), which focused primarily on depression, this study provides a broader perspective on the role of life satisfaction in SSc. Consequently, these results support the integration of life satisfaction assessment and interventions in SSc care, emphasizing the importance of a more comprehensive biopsychosocial approach. Finally, the researchers acknowledge limitations in this study, including high heterogeneity (I² = 62-78%) and potential publication bias. Future research should focus on longitudinal studies and the development of targeted interventions to enhance life satisfaction in SSc patients.